Cannabidiol attenuates OGD/R-induced damage by enhancing mitochondrial bioenergetics and modulating glucose metabolism via pentose-phosphate pathway in hippocampal neurons - Shanshan Sun (Redox Biology, 2017)
Deficient bioenergetics and diminished redox conservation have been implicated in the development of cerebral ischemia/reperfusion injury. In this study, the mechanisms underlying the neuroprotective effects of cannabidiol (CBD), a nonpsychotropic compound derived from Cannabis sativa with FDA-approved antiepilepsy properties, were studied in vitro using an oxygen–glucose-deprivation/reperfusion (OGD/R) model in a mouse hippocampal neuronal cell line. CBD supplementation during reperfusion rescued OGD/R-induced cell death, attenuated intracellular ROS generation and lipid peroxidation, and simultaneously reversed the abnormal changes in antioxidant biomarkers. Using the Seahorse XFe24 Extracellular Flux Analyzer, we found that CBD significantly improved basal respiration, ATP-linked oxygen consumption rate, and the spare respiratory capacity, and augmented glucose consumption in OGD/R-injured neurons. The activation of glucose 6-phosphate dehydrogenase and the preservation of the NADPH/NADP+ ratio implies that the pentose-phosphate pathway is stimulated by CBD, thus protecting hippocampal neurons from OGD/R injury. This study is the first to document the neuroprotective effects of CBD against OGD/R insult, which depend in part on attenuating oxidative stress, enhancing mitochondrial bioenergetics, and modulating glucose metabolism via the pentose-phosphate pathway, thus preserving both energy and the redox balance. Keywords: Cannabidiol, Ischemia/reperfusion, Mitochondrial bioenergetics, Pentose-phosphate pathway, Neuroprotection